Strategies in increasing fishermen’s catches in Pasongsongan Village, Pasongsongan District: Study UPT of coastal fishing ports - Nurlaily Wulandari; Rachmad Hidayat (Technium Social Sciences Journal, 2023)
UPT Coastal Fishing Port located in Pasongsongan Village, Pasongsongan District. The implementation of the strategy used to provide fishermen facilities and infrastructure with the aim of increasing fishermen’s catches, based on research I conducted at the UPT Coastal Fishing Port, the obstacles that are still experienced when counseling fishermen are not all elements join in socialization activities. The purpose of this study was to determine the Upt Strategy of Coastal Fishing Ports in Increasing Fishermen’s Catches in Pasongsongan Village, Pasongsongan Regency. This research was carried out at the UPT Coastal Fishing Port, Pasongsongan Village, Pasongsongan District. This type of research is qualitative research with descriptive methods, the data collection techniques used are observation techniques, interview techniques, documentation techniques The results of this study show that the strategic policies used by the UPT Coastal Fishing Port provide facilities for fishermen to continue to produce good fish catches.